1999
DOI: 10.1007/3-540-49059-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Automated Fast-Track Reconfiguration of Group Communication Systems

Abstract: We present formal techniques for improving the performance of modular communication systems. For common sequences of operations we identify a fast-path through a stack of communication protocols and reconfigure the system's code accordingly. Our techniques are implemented by tactics and theorems of the NuPRL proof development system and have been used successfully for the reconfiguration of application systems built with the Ensemble group communication toolkit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…This article extends preliminary work reported in (Kreitz, 1997;Kreitz et al, 1998;Kreitz, 1999), which now has matured into pushbutton technology and is based on an advanced semantical model for OCaml, which allows for a typetheoretical representation of a larger fragment of the programming language.…”
Section: Resultssupporting
confidence: 72%
“…This article extends preliminary work reported in (Kreitz, 1997;Kreitz et al, 1998;Kreitz, 1999), which now has matured into pushbutton technology and is based on an advanced semantical model for OCaml, which allows for a typetheoretical representation of a larger fragment of the programming language.…”
Section: Resultssupporting
confidence: 72%
“…In addition to aspects of theoretical developments and issues of implementing state-of-the-art proof environments there have been numerous applications ranging from mathematics and formal courseware to hardware and software design, verification, and optimization [1,18,19,28,34,56,62,64,68,77,79,80,85,86,96]. Much of our current research supports the interaction between Nuprl and other mathematical assistants, proof engines, and publication mechanisms-both from the technological and from the logical perspective-which will lead to a greater acceptance of these systems in the practice of mathematics and software development.…”
Section: Resultsmentioning
confidence: 99%
“…Using this methodology [Kre99], Kreitz, Hayden, ffickey, van Renesse and graduate student Xioaming Liu showed that Nuprl can automatically achieve protocol speedups comparable to the ones that Van Renesse achieved by hand in Horus. Moreover, Liu and Van Renesse developed an version of the method for use in adapting Ensemble to match the protocol stack to the environment.…”
Section: A Formal Transformation Of Protocol Stacksmentioning
confidence: 99%